THE EFFECT OF Averrhoa Bilimbi L (BELIMBING WULUH) GEL EXTRACT ON INCREASING DEGREE OF EETH BRIGHTNESS (IN VIVO) - Asih Rahaju; Zwista Yulia Dewi; Fikri Alatas; Kintan Putri Nur Shafarkiani (Fakultas Kedokteran Gigi Unjani, 2021)
Discoloration (extrinsic and intrinsic) reduce the beauty of someone's appearance and confidence. Discoloration affected the increased aesthetic treatment needs in dentistry. Discoloration can be treated by teeth whitening procedures. Teeth whitening can be done with dental bleaching from the application of chemicals on the surface of the teeth. However, dental bleaching has side effects such as reduce the amount of calcium, phosphate and fluoride in tooth enamel, reduce enamel hardness, enamel surface roughness, and dental hypersensitivity. Belimbing wuluh is one of the herbal ingredients to minimise the risk; it contains oxalic acid, a natural peroxide compound. This study purposed to determine the effect of belimbing wuluh gel extract in increasing the degree of teeth brightness colour by in vivo in rabbits. This study used an experimental analytic method with 27 rabbits' incisors, divided into three groups: 50% belimbing wuluh gel, 40% oxalic acid gel, and negative control group. Rabbits' incisors were previously coated in a transparent varnish on the specified area. Teeth bleaching is done for 4 hours in 14 days. Colour measurements used camera and ring-light, which MATLAB will convert. The data were analysed statistically with One way ANOVA followed by a post-hoc NSK test (p <0.05). The result showed that belimbing wuluh gel extract caused an increase in the teeth colour's brightness (p = 0.0030). So, it can be concluded that belimbing wuluh gel extract affects increasing the degree of teeth brightness. DOI : 10.54052/jhds.v1n1.p80-88